Pengaruh Strategi Pemasaran Digital Terhadap Keputusan Pembelian Produk Kesehatan Pada Masyarakat Kelurahan Mencirim Kecamatan Binjai Timur - Isnan Sarwo Prasetyo (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study focuses on an in-depth analysis of how digital marketing strategies influence the decisions of residents of Mencirim Village, East Binjai District in purchasing health products. The scope of digital marketing studied includes social media platforms, the effectiveness of online advertising, the depth of marketing content, and the role of electronic reviews or electronic word of mouth (e-WOM). Using a quantitative approach with a survey method, this study involved 100 respondents selected through a purposive sampling technique. The main criteria for respondents were residents aged at least 17 years who had actively transacted health products digitally in the last three months. Data were collected through a 5-point Likert scale questionnaire and processed using multiple linear regression analysis with the help of IBM SPSS Statistics 26. The research findings revealed that partially, social media (β = 0.312), online advertising (β = 0.287), marketing content (β = 0.241), and e-WOM (β = 0.198) had a positive and significant influence on consumer purchasing decisions (p < 0.05). Collectively, the integration of these four variables explains 68.4% (R² = 0.684) of the dynamics of local purchasing decisions.